Multi-Parallel Configuration of a Current Source AC/DC Ccnverter with Energy Recovery Snubber Circuits - NAKADE, Masanobu; ISE, Toshifumi; MURAKAMI, Yoshishige (The Japan Institute of Power Electronics, 1994)
Operating characteristics of a current source AC/DC converter circuit with enegy recovery snubbers and its multi-parallel configuration were studied in this paper. In the circuit, both di/dt and dv/dt stress on swiching devices are very low compared with conventional circuits, and energy in the snubber capacitors can be fully recovered. A multi-parallel configuration was studied in order to achieve high current handling capability and reducing harmonics. The multi-parallel configuration is a current source multi-level converter.